Two-objective Approach for Electrical Vehicles Parking lot Participation in Joint Energy, and Ancillary Services Markets - Nikpour, Ahmad; Nateghi, Abolfazl; Shafie-Khah, Miadreza (IEEE, 2023)
In response to having a green transport sector and increasing sustainable energy alternatives, it is expected that electric vehicles (EVs) will be a considerable energy consumer in the near future. In order to cover the problems related to their charging demand, the integration approaches between the EVs and the grid should be optimized. Electric vehicle parking lots (EVPLs) are an exceptional solution for managing the charging process of EVs. Moreover, vehicle-to-grid (V2G) feature has the potential of increasing the reliability of the power system, the profit of EVPLs (by providing ancillary services (AS)), and reducing the cost of EVs owners. In this paper, an incentive-based two-objective approach is suggested for optimizing the profit of EVPLs and EV owners (each vehicle individually) by participating in day-ahead (DA) electricity and AS markets at the same time. Probability distribution functions (PDF) and random data are used to cover uncertainties. The suggested method is tested using the real word data by GAMS solvers.
Keywords: Ancillary services; Electrical vehicles parking lot; Optimal bidding; Regulation up; Regulation down; fi=Sähkötekniikka|en=Electrical Engineering|